A conformational switch controls cell wall remodeling enzymes required for bacterial cell division - Yang, Desirée C. (2012)
Remodeling of the peptidoglycan (PG) exoskeleton is intimately tied to the growth and division of bacteria. Enzymes that hydrolyze PG are critical for these processes, but their activities must be tightly regulated to prevent the generation of lethal breaches in the PG matrix. Despite their importance, the mechanisms regulating PG hydrolase activity have remained elusive. Here we investigate the control of cell division hydrolases called amidases (AmiA, AmiB, and AmiC) required for Escherichia coli cell division. Poorly regulated amiB mutants were isolated encoding lytic AmiB variants with elevated basal PG hydrolase activities in vitro. The structure of an AmiB ortholog was also solved, revealing that the active site of AmiB is occluded by a conserved alpha-helix. Strikingly, most of the amino acid substitutions in the lytic AmiB variants mapped to this domain and are predicted to disrupt its interaction with the active site. Our results therefore support a model in which cell separation is stimulated by the reversible relief of amidase auto-inhibition governed by conserved sub-complexes within the cytokinetic ring. Analogous conformational control mechanisms are likely to be part of a general strategy used to control PG hydrolases present within multi-enzyme PG remodeling machines.